2015
DOI: 10.1117/12.2180466
|View full text |Cite
|
Sign up to set email alerts
|

Surface-enhanced Raman scattering from living cells: from differentiating healthy and cancerous cell to cytotoxicity assessment

Abstract: There is an ongoing effort to obtain molecular level information from living cells using surface-enhanced Raman scattering (SERS) not only to understand changes of cellular processes upon exposure to external stimuli but also to decide the status of cells; whether they are healthy or abnormal. In our research effort, we investigate how much information can be obtained from living cells to use for decision making about the cellular processes using SERS. The undertaken studies include cytotoxicity assessment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Later, the detection of different cancer types with the technique was reported [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. We also demonstrated that SERS could successfully differentiate cancerous tissues and cells from controls in our previous studies [ 50 , 51 , 52 ]. Even in a comparison of SERS and Raman spectroscopy for the detection of breast cancer from serum samples found that SERS was more successful [ 53 ].…”
Section: Introductionsupporting
confidence: 61%
“…Later, the detection of different cancer types with the technique was reported [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. We also demonstrated that SERS could successfully differentiate cancerous tissues and cells from controls in our previous studies [ 50 , 51 , 52 ]. Even in a comparison of SERS and Raman spectroscopy for the detection of breast cancer from serum samples found that SERS was more successful [ 53 ].…”
Section: Introductionsupporting
confidence: 61%